CONSTRAINTS IN FISH FARMING PRACTICES IN UTTAR PRADESH, INDIA-AN ANALYSIS - Dewan, Ritu; Pandey, S. K. (Journal of Indian Fisheries Association, 2015)
Aquaculture can be considered as a rapidly growing sector in many Indianstates including Uttar Pradesh. The impressive overall upward trendÂ· in fishproduction is likely to continue in future years as there are plenty ofunutilizedor underutilized fishery resources in the state. In spite of the growingpopularity of aquaculture in the state, fish farmers have been experiencingfinancial, social and technical constraints in fish farming practic~s. Theseconstraints are adversely affecting farmers in obtaining expected fish yieldsand income. In this study, the most common problem areas were identified,analysed and ranked on the basis of farmers' perception.Keywords: Fish farming, constraints, ranking, credit, seed, input price,subsidy, knowledge